A Fabry-Pérot cavity coupled surface plasmon photodiode for electrical biomolecular sensing - Giles Allison; Amrita Kumar Sana; Yuta Ogawa; Hidemi Kato; Kosei Ueno; Hiroaki Misawa; Koki Hayashi; Hironori Suzuki (Nature Communications, 2021)
Surface plasmon resonance is well established for biosensing applications, but commonly limited by complex optical detection. Here, the authors present a plasmonic sensor integrated in a photovoltaic cell, which generates an electronic signal sensitive to the solution refractive index via plasmon interaction